Método implícito para solução do problema de ondas de cheia em junção de rios - Silva, Paulo Cristóvão de Araújo (1972)
The scope of this thesis is to propose and analyse a new method for problems of flood waves through junctions of rivers or channels. It can be summarized as follows: 1) we assume that each branch can be cut at the junction and analysed independently of the others, using an implicit method; 2) matching the stages at the junction using the continuity equation. Besides other features related to the method it is worthwhile to emphasize: a) it is impossible to solve the problem by approximate methods known at the present time (1972). b) the only solution presented in a systematic way, makes use of an explicit method jeopardized by crucial restrictions. This thesis follows the following outline: I) Description of important applied problems concerning flood movement and definition of the scope of this study; II) Basic theory, historical review of the solutions methods, more frequently used methods, their advantages and limitations; III) Description of Amein and Fang's Implicit Method for problems of floods movement, applications and advantages; IV) Analysis of the junction problem and development of a solution by cutting the branches at the junction; V) Presentation of the results and comments on the practical application of this method. The Conclusions presented in the text justify the feasibility and usefulness of the method. Applications to real problems depends only on field data (disposibility and codification). Related to some problems that came into play during the present study, we make some suggestions for further research. In the Appendix are exposed some comments on the computer programs, flow charts and listings.